Design and function of GaN MESFET terahertz signal generator by finite difference method. (April 2017) - Kodigala, Subba Ramaiah; Chattopadhyay, Somnath; Overton, Charles B.
Abstract: The GaN based metal semiconductor field effect transistor (MESFET) devices have been designed by employing finite difference method in order to fit quite well for generation of terahertz signals. The equipotential and equi-electric field contours are broadly developed with variation of drain and gate voltages. The motion of Gunn domain with variation of voltage is constantly observed from source to drain in the channel area of MESFET. In fact, the domain is more clearly visible in the equi-electric field contours than that in the equipotential contours. The distribution of electron concentration ( n ) in the MESFET is also determined in the steady state mode by fitting right successive relaxation factor and electron relaxation time. The I-V curves of drain are tested by employing Gummel process in finite difference method. The MESFET device is designed in such way to obtain 26.5 GHz output signal in the millimeter region by tailoring its physical parameters such as geometry of device, carrier concentration, mobilities etc.